Comparison of structural and optical properties of zinc oxide and silver doped zinc oxide thin films at various layers using spin coating technique - Azra Shakira, Hassan (2016)
Pure zinc oxide (ZnO) and Ag-doped Zno (SZO) thin films were fabricated and deposited on glass substrate by sol-gel method and spin coating technique. The crystalline structure, optical transmittance and surface morphology were investigated as a function of different deposition layer. The films were subjected to annealing temperature of 300 °C. ZnO and SZO shows the dominance in the (1 0 1) direction. As the deposition number increases, the crystallinity increased meanwhile the transmittance shows a valuable results since only 10 drops of dopant could improve the optical characteristics up to 90 %. ZnO thin film shows an even distribution at 3 layers deposition when subjected to 3000 rpm spin coating and chromosome-like structure were obtained at 11 layers deposition of SZO subjected to the same parameter of spin coating technique.